An Indoor Resource Optimisation using Ray-Tracing Techniques and Signal-To-Interference Object Function to Obtain Best Capacity - KENNY, EAMONN; O NUALLAIN, EAMONN (My University, 2014)
The purpose of this work is to produce a method that calculates the best locations of a multiple transmitters in an indoor environment whilst meeting the required user capacity. The method uses a non-standard building discretisation and a signal-to-interference ratio with quasi-convex space optimisation to produce the best positioning of transmitters.
IEEE Conference on Electromagnetic Field Computation
PUBLISHED
Annecy, France
Keywords: Propagation; Optimisation; Ray-tracing; Telecommunications